Europe’s Future Is Digital: A Broad Vision of the Industry 4.0 Concept beyond Direct Manufacturing in the Company - Liviu Moldovan; Adrian Gligor (Proceedings, 2020)
These proceedings contain research papers that were accepted for presentation at the 14th International Conference Inter-Eng 2020 “Interdisciplinarity in Engineering”, which was held on 8–9 October 2020, in the city of Târgu Mureș, Romania [...]